Synthesis, stereocomplex crystallization and homo-crystallization of enantiomeric poly(lactic acid-co-alanine)s with ester and amide linkages. Issue 5 (11th January 2018) - Tsuji, Hideto; Sato, Shotaro; Masaki, Noriaki; Arakawa, Yuki; Kuzuya, Akinori; Ohya, Yuichi
Abstract : α-Hydroxy acid and α-amino acid-derived poly(l -lactic acid- co -l -alanine)s and poly(d -lactic acid- co -d -alanine)s with different alanine unit contents were synthesized and their stereocomplex crystallization and homo-crystallization were investigated. Abstract : α-Hydroxy acid and α-amino acid-derived poly(l -lactic acid- co -l -alanine)s and poly(d -lactic acid- co -d -alanine)s with different alanine unit contents were synthesized by copolymerization ofl -lactide and (3 S, 6 S )-3, 6-dimethyl-morpholine-2, 5-dione and ofd -lactide and (3 R, 6 R )-3, 6-dimethyl-morpholine-2, 5-dione, respectively. The effects of the incorporated alanine units in lactic acid units or amide linkages in ester linkages on the crystallization behavior of solution- and melt-crystallized 50/50 blended samples as well as that of solution- and melt-crystallized nonblended samples were investigated. This article reports for the first time a stereocomplex (SC) formation between enantiomeric random copolyesteramides poly(lactic acid- co -alanine)s with ester and amide linkages. The solution-crystallized nonblended samples crystallized in α- or δ-form homo-crystallites for anl -alanine unit content up to 6 mol% or ad -alanine unit content up to 3 mol%, whereas all the melt-crystallized samples crystallized in α- or δ-form homo-crystallites for thel - ord -alanine unit content at least up to 12 and 13 mol%. In contrast, the solution-crystallized blended samples with the alanine unit contents of 0–13 mol% and the melt-crystallized blended samples with the alanine unit contents of 4–13 mol% crystallized only in SC crystallites, whereas the melt-crystallized blended samples with an alanine unit content of 0 mol% [ i.e., poly(l -lactic acid)/poly(d -lactic acid) blends] crystallized in both SC crystallites and homo-crystallites. The alanine units of melt-crystallized nonblended samples were incorporated into homo-crystalline regions, whereas those of solution-crystallized nonblended samples were excluded from homo-crystalline regions. In contrast, the alanine units of solution-crystallized blended samples were incorporated into SC crystalline regions, whereas those of melt-crystallized blended samples were excluded from SC crystalline regions.